Clinical evaluation of marketed and non-marketed orthodontic products: are researchers now ahead of the times? A meta-epidemiological study - Almaha Alhussain; Martyn T. Cobourne; Nikolaos Pandis; Jadbinder Seehra (Progress in Orthodontics, 2023)
Abstract Background The advertisement and adoption of untested orthodontic products is common. This study aimed to provide an update regarding the prevalence of clinical trials in orthodontics evaluating commercially marketed products. Associations between marketed/non-marketed products and study characteristics such as direction of effect, declaration of conflict of interest and industry sponsorship were evaluated. In addition, within the marketed products associations between direction of effect and study characteristics were explored. Material and methods Electronic searching of a single database (Medline via PubMed) was undertaken to identify Randomized controlled trials (RCTs) published over a 5-year period (1st January 2017 to 31st December 2021). Descriptive statistics and associations between trial characteristics were explored. Results 196 RCTs were analysed. RCTs were frequently published in Angle Orthodontist (18.4%), American Journal of Orthodontics and Dentofacial Orthopedics (14.8%) and European Journal of Orthodontics (13.3%). 65.3% (128/196) of trials assessed marketed products after their introduction. The majority of trials assessed interventions to improve treatment efficiency (33.7%). Growth modification appliances were typically analysed in non-marketed compared to marketed products. An association between the type of product (marketed vs non-marketed) and both the declaration of conflict of interest and industry sponsorship was detected. For individual RCTs assessing marketed products either a positive effect (45.3%) or equivalence between interventions or between intervention and untreated control (47.7%) was evident. In 27% of these trials either no conflict of interest or industry funding was not clearly declared. Within the marketed products, no association between the direction of the effect and conflict of interest or funding was detected. Conclusions The analysis of marketed orthodontic products after their introduction is still common practice. To reduce research waste, collaboration prior to the licensing and marketing of orthodontic products between researchers, industry and manufacturers is recommended.